LINGUISTIK SYAHRUR MEREKOSTRUKSI HUKUM ISLAM - Elkarimah, Mia Fitriah (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2015)
Muslims believe that the Qur?an is authored and revealed by God. It contains Islamic principles, values, and norms by which human should embrace. Therefore the Qur?an is framed in the light of many perspective or approach. Inspite of linguistic approach. this Holy Scripture develops in the form of human experiences as the language it uses is Arabic. This later understanding leads some Qur?anic experts to expand the study of the Qur?an in the lights of linguistic analysis. The purpose of this research is mapping and describing the concept Syahrur in reviewing texts of the Qur'an by using language approach (linguistic) and the implications of such an approach to Islamic law.Syahrur would to show the public that the assessment the texts of the Qur'an with the linguistic approach is the potential for dinamitating words and phrases in the Qur `an and will give the progressive, liberate, and humanist Islamic interpretation.This reseach used library research models, and focus on analytical descriptions. The aim is elaborating of Syahrur?s linguistic approach. And the terms in linguistics will help clarify the exposition of Syahrur?s linguistic concepts against Islamic law